40Ar-39Ar ages of dolerite dykes from Sri Lanka - Takigami, Yutaka; Yoshida, Masaru; Funaki, Minoru (National Institute of Polar Research, 1999)
P(論文) Two ^<40>Ar-^<39>Ar ages were obtained for dolerites from Sri Lanka which had been dated by the K-Ar method as 143-152 Ma. ^<40>Ar-^<39>Ar ages, which are more reliable than the K-Ar ages, are 160-170 Ma. These ages are important for constraining the scenario of break-up of Gondwana in the early Jurassic period. departmental bulletin paper